THE ESSENCE OF 'AQL AS KAMĀL AL-AWWAL IN THE VIEW OF IBNU SĪNĀ - Abdul Rohman; Amir Reza Kusuma; Muhammad Ari Firdausi (IAIN Ponorogo, 2022)
This article aims to examine the essence of 'aql as kamāl al-awwal in Ibn Sīnā's philosophy. In this article, the author uses a qualitative research method with a descriptive-analytical and philosophical approach. This study found several important points which include: first, 'aql by Ibn Sīnā is defined as a potential of nafs insāniyyah or nafs nāṭiqah which helps humans to achieve knowledge and truth; secondly, the essence of 'aql for Ibn Sīnā is kamāl al-awwal, therefore it is immaterial and not material; third, the essence of 'aql as kamāl al-awwal makes it correlate with the nafs, rūḥ, and qalb which are human spiritual entities; fourth, 'aql as kamāl al-awwal also shows its potential as a tool to gain knowledge, where the process begins with the capture of phenomena through the five senses and then digested by 'aql and assisted in conceptualizing it through the emission of 'Aql Fa'āl; fifth, Ibn Sīnā's idea of the essence of 'aql may have been influenced by earlier Muslim philosophers such as al-Kindī and al-Fārābī, besides having undergone several explorations. In addition, he also succeeded in influencing later Muslim philosophers such as al-Ghazālī. is something that settles in life and appears in the action easily without the need of thinking first. Morals are not deeds, strengths, and knowledge. Morals are